(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The manuscript 16 of the Accademia dell’Arcadia contains both a Genealogia and a Albero Genealogico dei Re d’Arcadia. The sheets likely date from the early years of the Academy, when the Arcadians were writing a succinct history of Arcadia which retraced the stages through which the Coetus had structured itself as a Republic from its legendary origins, that is from when Evander had arrived on the Palatine Hill along with the ancient Arcadians. The reforms of the time and the creation of a Greek-inspired Ephemeris, as well as the memory of the cult of the indigenous deities, reflect the founders’ desire to give the assembly a prestigious mythical origin. Such a legacy soon manifested itself in the prose and poetry of the Academy, especially in those compositions that the Arcadians read at the Bosco Parrasio on the Palatine Hill, a place they arrived at, somewhat like Evander, after various wanderings and where they would promulgate the Leges in 1696.